Caregivers’ Grief in Acquired Non-death Interpersonal Loss (NoDIL): A Process Based Model With Implications for Theory, Research, and Intervention - Yehene, Einat; Manevich, Alexander; Rubin, Simon Shimshon (Frontiers in Psychology, 2021)
The number of family members caring and caregiving for a loved one undergoing physical and mental changes continues to increase dramatically. For many, this ongoing experience not only involves the “burden of caregiving” but also the “burden of grief” as their loved-one`s newfound medical condition can result in the loss of the person they previously knew. Dramatic cognitive, behavioral and personality changes, often leave caregivers bereft of the significant relationship they shared with the affected person prior to the illness or injury. This results in what we term conditions of acquired “non-death interpersonal loss” (NoDIL). Current approaches to these losses use an amalgam of models drawn from both death and non-death loss. Despite their utility, these frameworks have not adequately addressed the unique processes occurring in the interpersonal sphere where the grieving caregiver needs to reach some modus vivendi regarding the triad of “who the person was”, “who they are now” and “who they will yet become”. In this paper we propose a process-based model which addresses cognitive-emotional-behavioral challenges caregivers meet in the face of their new reality. These require a revision of the interpersonal schemas and the relationships that takes into account the ongoing interactions with the affected family member. The model and its utility to identify adaptive and maladaptive responses to NoDIL is elaborated upon with clinical material obtained from caregivers of people diagnosed with major neuro-cognitive disorder and pediatric traumatic brain injury. The article concludes with implications for theory, research and clinical intervention.